THE INFLUENCE OF AUDITORY AND VISUAL PRODUCTS ON CONSUMER PURCHASE DECISIONS (Study on Consumers of Local Coffee Shop in Semilir Semarang) - Imam Gozali; Fira Salsabila Zahroh (Proceeding of The International Conference on Business and Economics, 2023)
This study aims to determine the effect of auditory and visual products on consumer purchasing decisions at local coffee shops in Semilir Semarang in 2021. The data in this study are primary data from questionnaires with 100 respondents at local coffee shops in Semilir Semarang, using accidental sampling. The analytical tool used is Multiple Linear Regression analysis. The results of the study show that Auditory and Visual Products have a significant positive effect on consumer purchasing decisions.